The two faces of January [videorecording (DVD)] - Amini, Hossein; Mortensen, Viggo, 1958-; Dunst, Kirsten, 1982-; Isaac, Oscar; Highsmith, Patricia, 1921-1995 ([Publisher not identified], 2015)
Sleek thriller set in Greece and Istanbul in 1962. Intrigue begins at the Parthenon when wealthy American tourists Chester MacFarland and his young wife Collete meet American ex-pat Rydal, a scammer working as a tour guide. The two befriend him, but a murder at the couple's hotel puts all three on the run together and creates a precarious bond between them as the trio's allegiance is put to the test.